New locals or the newly-migrantized? The markers of the internally displaced populations’ visibility in Ukraine - Balinchenko, Svitlana (Przeglad Wschodnioeuropejski, 2023)
The article analyzes internal displacement with attention to the visibility of the displaced populations in the host communities. The study is based on the Ukraine case of protracted internal displacement, during the 2014-2021 period, from the beginning of the Russo-Ukrainian war, and just before the full-scale Russian invasion of Ukraine. It employs the methodology of Causal Layered Analysis and secondary analysis of the national survey data on internal displacement. Regarding the distortions of visibility, I suggest hypovisibility (anopticism) and hypervisibility (panopticism), through the VASE-approach that includes visibility, access to decision-making, sense of belonging, and estimation of common perspectives as the indicators of adaptation of the newcomers in the receiving communities. The visibility of the displaced populations is reviewed through the systemic and myth/metaphor levels. The labels of “burden”, “problem” or “capital” applied to the displaced populations in the narratives and official documents are referred to as a visibility-related issue that has an impact on social cohesion.